2019
DOI: 10.19080/ctoij.2019.13.555857
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Computed Tomography (CT) And Magnetic Resonance Imaging (MRI) Based Radiosurgery Treatment Planning for Pituitary Adenomas

Abstract: Aim: Pituitary adenomas are fairly common benign tumors which may be found in up to 20% of the general population. While a considerable proportion of patients harboring these benign tumors may be asymptomatic, symptoms may arise due to the mass effect on critical neurovascular structures including the optic nerves and chiasm, cavernous sinus, and normally functioning pituitary gland or stalk. Radiosurgery may be used as a viable therapeutic option for management of pituitary adenomas. Treatment planing for rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Utility of multimodality imaging for radiosurgery treatment planning for tectal gliomas has been poorly addressed in the literature. In this context, our study adds to the existing literature and supports the incorporation of MRI for improved radiosurgery treatment planning for tectal gliomas consistent with another studies [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…Utility of multimodality imaging for radiosurgery treatment planning for tectal gliomas has been poorly addressed in the literature. In this context, our study adds to the existing literature and supports the incorporation of MRI for improved radiosurgery treatment planning for tectal gliomas consistent with another studies [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we assessed incorporation of multimodality imaging into target volume definition of trigeminal neuralgia radiosurgery. Indeed, usefulness of neuroimaging with MRI for definition of central nervous system radiotherapy and radiosurgery target volumes has been an important focus of research in the literature [40][41][42][43][44][45][46][47][48][49]. Our results appear to be compatible to these studies supporting the incorporation of MRI in radiosurgery treatment planning.…”
Section: Discussionsupporting
confidence: 84%
“…Axial MRI of intracranial GCT is demonstrated on Figure 2. [32][33][34][35][36][37][38][39]. In the context of intracranial GCT management, irradiation with less extensive treatment portals and lower doses has been investigated for improved normal tissue sparing and quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, multimodality imaging may add to the accuracy of target definition for radiosurgery of intracranial GCTs. Indeed several other studies have demonstrated refined treatment volume determination by including MRI to the process of target determination [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%